2017
DOI: 10.1111/cei.12969
|View full text |Cite
|
Sign up to set email alerts
|

Chimerism-based tolerance in organ transplantation: preclinical and clinical studies

Abstract: SummaryInduction of allograft tolerance has been considered the ultimate goal in organ transplantation. Although numerous protocols to induce allograft tolerance have been reported in mice, a chimerism-based approach through donor haematopoietic stem cell transplantation has been the only approach to date that induced allograft tolerance reproducibly following kidney transplantation in man. Renal allograft tolerance has been achieved by induction of either transient mixed chimerism or persistent full donor chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 55 publications
0
37
0
2
Order By: Relevance
“…Of the 10 recipients enrolled in the studies, all developed transient mixed chimerism and immunosuppression was discontinued in eight patients. After a follow-up period of 7-14 years, four patients still could discontinue immunosuppression completely (62).…”
Section: Clinical Application To Kidney Transplantationmentioning
confidence: 96%
“…Of the 10 recipients enrolled in the studies, all developed transient mixed chimerism and immunosuppression was discontinued in eight patients. After a follow-up period of 7-14 years, four patients still could discontinue immunosuppression completely (62).…”
Section: Clinical Application To Kidney Transplantationmentioning
confidence: 96%
“…115 The notion of inducing hematopoietic chimerism for establishing immune tolerance to solid organ transplantation has been since brought to test in numerous clinical trials, and has shown great efficacy in allograft protection. [116][117][118] Hematopoietic chimerism is a form of central tolerance whose mechanisms of tolerance primarily involve clonal deletion of donor-reactive T cells and B cells in the thymus and bone marrow, respectively. 119,120 However, this tolerance approach often requires aggressive recipient bone marrow conditioning regimens and further, exposes recipients to long-term risks for graft-versus-host disease.…”
Section: A B Rief Overvie W Of Peripher Al Toler An Ce Induc Ti On mentioning
confidence: 99%
“…Cyclosporine or Tacrolimus was slowly tapered over several months and completely discontinued at 8 months after confirming freedom from rejection by a 6-month protocol biopsy. All (10/10) patients developed transient chimerism and seven patients achieved tolerance from which four remain completely off immunosuppression (5–13 years) ( 9 , 78 , 80 ). To reduce the toxicity of the regimen and to ameliorate the engraftment syndrome cyclophosphamide has recently been substituted by TBI (2 × 150 cGy).…”
Section: Current State Of Affairsmentioning
confidence: 99%
“…So far two patients have been treated with this modified protocol, from which one remains off immunosuppression for more than 3 years. Future trials are expected to include the use of belatacept, based on murine ( 81 , 82 ) and non-human primate studies ( 79 , 80 , 83 ).…”
Section: Current State Of Affairsmentioning
confidence: 99%